Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

Aux marges de l'emploi: parcours de travailleuses domestiques québécoises, 1950-2000 - Charron, Catherine (Les éditions du remue-ménage, 2018)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; travail; travail domestique

Au-delà du plaisir visuel: féminisme, énigmes, cinéphilie - Mulvey, Laura (Formes filmiques, 2017)
En 1975, Laura Mulvey publie Plaisir visuel et cinéma narratif, texte polémique qui met en lumière la manière dont la forme filmique serait structurée par l’inconscient de la société patriarcale. C’est l’essai fondateur des études féministes sur le cinéma. Rédigés entre 1975 et 2011, les textes choisis dans ce volume sont marqués par la redécouverte féministe de la psychanalyse et les transformations induites par le développement des technologies numériques. Qu’elle s’attache à des genres ou à des auteurs incontournables (le western, le mélodrame, Ophüls, Hitchcock, Godard), qu’elle incarne l’avènement d’un « spectateur pensif », qu’elle analyse les paradoxes de l’esthétique hollywoodienne ou la compilation de films de propagande coloniale, Laura Mulvey fait preuve d’une cinéphilie active et engagée.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; cinema hollywoodien; cinéma; com5170; communication; corps; cours; discipline; discours dominant; europe; har4600; histoire de l'art; histoire et politique; male gaze; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; regard masculin; royaume-uni; régions géographiques; sofia; systèmes d'oppressions; thématiques; théorie du cinéma; états-unis

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Vote, ovocytes et cosmétiques. Les trois jalons identitaires du recours au genre dans la recherche sur les cellules souches en Californie - Thompson, Charis; Sofio, Séverine (Cahiers du Genre, 2014)
Cet article explore les trois jalons identitaires du recours au genre [punctuated gendering] dans la recherche biomédicale sur les cellules souches en Californie. J’y défends l’idée selon laquelle le développement de ce secteur a eu besoin des femmes à trois reprises, mais pas de toutes les femmes à chaque fois. En d’autres termes, suivant les étapes que franchissait le développement de l’innovation autour des cellules souches, les femmes ont été sollicitées en fonction d’une perception du genre à chaque fois différente. Ainsi, il a d’abord fallu faire appel à elles en tant que citoyennes, au croisement des rapports de sexe, de race et de classe ; on a ensuite eu besoin d’elles en tant que corps biologiques ; elles ont, enfin, été sollicitées en tant que consommatrices. Le but de ce triple recours aux femmes selon des identités de genre à chaque fois spécifiques, fut d’abord d’attirer des capitaux publics et privés dans ce secteur, une fois le soutien de l’état californien garanti ; puis d’assurer l’approvisionnement de la recherche en morceaux de corps humain ; et enfin, de permettre le développement de l’économie autour de l’innovation sur les cellules souches. Cet article s’appuie sur mes précédents travaux sur la biomédicalisation et la marchandisation de la reproduction, mais il s’inscrit également dans la perspective des théories de la division sexuée du travail, et de la construction sociale du genre par la publicité et la consommation. Au croisement de ces logiques, l’innovation biomédicale apparaît donc comme un espace privilégié pour étudier le genre comme répertoire identitaire dynamique, à travers une mise en œuvre concrète de l’idée d’intersectionnalité.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; intersectionnalité; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Enjeux culturels et sociaux de la circulation de la chanson J’attendrai dans les années 1940 - Beaudet, Simon-Pierre; Savoie, Chantal (Mens. Revue d'histoire intellectuelle et culturelle, 2013)
Cette analyse aborde le cas singulier de la circulation de la chanson J’attendrai dans la culture des années 1940, dont l’analyse des variantes permet de cerner les rapports mouvants d’une chanson aux genres chansonniers et musicaux, aux goûts et aux pratiques du public, ainsi qu’à leur ancrage au sein des champs culturels nationaux. Elle permet même, parfois, de sonder les modalités de l’évolution des modèles des rapports sociaux entre les sexes présents dans différentes versions. Ce sont ainsi autant les enjeux artistiques, culturels, sociaux et intimes à l’oeuvre qui guident notre analyse de ce cas de transfert culturel, que le repérage de vecteurs permettant de formuler une équation de la circulation culturelle des chansons à succès.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1990-1999; amérique du nord; amériques; approches et analyses; arts; canada; chanson; culture populaire; discipline; histoire et politique; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; études littéraires

De la cuisine au studio - Lupien, Anna (Les éditions du remue-ménage, 2012)
De la cuisine au studio explore les parcours de douze artistes issues de trois générations différentes : femmes signataires du manifeste Refus global en 1948, premières cinéastes qui ont œuvré à l’ONF dans les années 1970 et artistes médiatiques impliquées au Studio XX. À partir d’entrevues avec les artistes, Anna Lupien pose un regard sociologique sur l’expérience de créatrices qui ont investi l’art en tant qu’espace d’expression dans la sphère publique. De quelle façon ont-elles élaboré des stratégies créatives et par le fait même donné corps à des transformations sociales engendrées par le mouvement féministe, notamment en ce qui a trait à la conciliation travail-famille ? Comment ont-elles intégré des milieux artistiques qui ne leur étaient pas ouverts d’emblée ? Comment se sont-elles engagées pour le bien commun à travers leur parcours artistique ? Les histoires de ces artistes – Madeleine Arbour, Christine Brault, Mireille Dansereau, Dorothy Todd Hénaut, Stéphanie Lagueux, Bérengère Marin-Dubuard, Helena Martin Franco, Terre Nash, Anne-Claire Poirier, Françoise Riopelle, Bonnie Sherr Klein et Françoise Sullivan – témoignent des luttes inachevées du mouvement féministe et des brèches qu’elles ont pratiquées dans l’ordre des choses, suscitant des rencontres originales entre l’art et le politiqu
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; conciliation famille-travail; discipline; famille; femmes* artistes; féminisme matérialiste; histoire et politique; militance; patriarcat; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis

Ces corps qui comptent : de la matérialité et des limites discursives du sexe - Butler, Judith (Éditions Amsterdam, 2009)
Traduction de Bodies That Matter, (1993) La prise en compte de la matérialité des corps n’implique pas la saisie d’une réalité pure, naturelle, derrière le genre : si le sexe est un présupposé nécessaire du genre, nous n’aurons jamais accès au réel du sexe qu’à travers nos schèmes culturels. Le sexe, comme le genre, est une norme culturelle, qui régit la matérialité des corps. Il importe donc de souligner que le concept de matière a une histoire, où sont sédimentés les discours sur la différence sexuelle. En outre, si certains corps (par exemple blancs, mâles et hétérosexuels) sont valorisés par la norme, d’autres (par exemple lesbiens ou non blancs) sont produits comme abjects, rejetés dans un dehors invivable. À travers une reprise critique du concept foucaldien de « contrainte productive », Judith Butler s’efforce, loin de tout volontarisme, de ressaisir la façon dont ces corps peuvent défaire les normes qui les constituent et devenir le lieu d’une puissance d’agir transformatrice. Ce livre, où l’épistémologie se mêle à la politique, constitue un jalon des études de genre et l’un des ouvrages majeurs de son auteure.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; art contemporain; corps; cours; culture; discipline; fem1000; genre; hétérosexisme; identités LGBTQIA2+; lit4700; maternité; philosophie; pol4212; politique; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe; soc2014; systèmes d'oppressions; thématiques; épistémologie; épistémologie queer; états-unis; études culturelles

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (Worlds of desire, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis